Why does institutionalised care not appeal to Indian families? Legislative and social answers from urban India - Brijnath, Bianca (Cambridge University Press, 2012)
In India, although notions of ageing and care are changing, there is a continued preference among families for home-based care of elderly relatives. The legislative policies and cultural practices that shape this preference will be examined in this paper with specific reference to aged-care facilities and the 2007 Maintenance and Welfare of Parents and Senior Citizens Act. Using qualitative data from a study on dementia care in urban India it will be shown how the Act and old-age homes are understood and experienced by Indian families and key service providers. In juxtaposing policy and practice it will be argued that while notions of care are being redefined by processes like migration and urbanisation, the preference for home care remains, indicating that existing services need to be re-oriented and expanded to support families in providing this care.